2007
DOI: 10.1074/jbc.m609066200
|View full text |Cite
|
Sign up to set email alerts
|

Role of RAD51C and XRCC3 in Genetic Recombination and DNA Repair

Abstract: In germ line cells, recombination is required for gene reassortment and proper chromosome segregation at meiosis, whereas in somatic cells it provides an important mechanism for the repair of DNA double-strand breaks. Five proteins (RAD51B, RAD51C, RAD51D, XRCC2, and XRCC3) that share homology with RAD51 recombinase and are known as the RAD51 paralogs are important for recombinational repair, as paralog-defective cell lines exhibit spontaneous chromosomal aberrations, defective DNA repair, and reduced gene tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
82
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(86 citation statements)
references
References 44 publications
1
82
0
1
Order By: Relevance
“…Indeed, XRCC3 depletion also was found to affect CHK2 phosphorylation (20). The CX3 complex also has been implicated in late stages of HR (54). However, mechanistically how the CX3 complex controls these independent functions requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, XRCC3 depletion also was found to affect CHK2 phosphorylation (20). The CX3 complex also has been implicated in late stages of HR (54). However, mechanistically how the CX3 complex controls these independent functions requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…XRCC3 is thought to participate in the resolvase step and RAD51C in both the resolvase step and in presynapsis of HR repair [24][25]. Thus, our data strongly suggest that DNA double strand breaks, associated with DNA replication, underlie Cr(VI)-induced chromatid aberrations, particularly chromatid exchanges.…”
Section: Discussionmentioning
confidence: 53%
“…XRCC3 is thought to participate in the resolvase step of HR repair and RAD51C is thought to participate in both the resolvase step and in presynapsis [24][25]. It is unknown if either of these genes are is involved in preventing Cr(VI)-induced CIN.…”
Section: Introductionmentioning
confidence: 99%
“…Some previous reports that have described the interaction between RAD51C and XRCC3, and the role of RAD51C in the resolution of homologous recombination intermediates have also been evaluated (15,31). In addition, some studies have suggested that RAD51C expression can affect XRCC3 expression.…”
Section: Discussionmentioning
confidence: 99%